Evaluation of Different Heat Processing Methods on the Nutritive Value of Mucuna pruriens (Velvet Bean) Seed Meals for Broilers - Emenalom, O.O.; Udedibie, A.B.I. (International Journal of Poultry Science, 2005)
Mucuna pruriens like most tropical legumes contain anti-nutritional factors, which limit its use as livestock feed ingredient. Proximate analysis and two performance studies using finisher broilers were carried out to determine the nutritive value of raw, toasted, cooked and, soak and cooked Mucuna (SACM). M pruriens seeds were ground raw, ground and toasted, and cooked prior to drying and midling in Experiment 1 and soaked in water for 48 hours prior to cooking for one hour before drying and milling in Experiment 2. Toasting increased the crude protein of the raw seed by 6.5% but decreased the ether extract by 22.9%. Cooking and soaking prior to cooking decreased the values for crude protein and ether extract by 5.3 and 6.5%, and 13.7 and 20.6%, respectively. In Experiment 1, 100gkg-1 raw, toasted, cooked and 200gkg-1 SACM were substituted into nutritionally balanced rations fed 28 to 56d of age. Mucuna seed meals caused progressive reductions in growth; at 56d of age broilers fed 100gkg-1 raw, toasted, cooked and 200gkg-1 cooked Mucuna grew 61.8, 67.2, 80.4 and 63.7% of control, respectively. Feed intake declined significantly with 100gkg-1 toasted and 200gkg-1 cooked MSM respectively. Feed to gain ratio decreased significantly (P< 0.05) with 100gkg-1 raw, toasted and 200gkg-1 cooked Mucuna, respectively. The heart, liver, kidney and gizzard weights relative to body weights were significantly (P< 0.05) affected by the diets. In Experiment 2, 200gkg-1 and 300gkg-1 dietary levels of Nigerian and Brazilian SACM were fed 28 to 56d respectively. With 300gkg-1 broilers grew significantly (P< 0.05) slower than the control and 200gkg-1 diet groups but feed intakes were unchanged. Inclusion of 200gkg-1 of the meals, allowed better growth than 300gkg-1 and by 56d of age growth were significantly (P< 0.05) depressed relative to control. At 200 and 300gkg-1 both Nigerian and Brazilian SACM promoted much better growth and efficiency than the raw Mucuna in Experiment 1 but values were significantly lower than those of controls. With 200gkg-1 broilers grew to 87.2 and 89.2% of controls respectively, a marked improvement over cooked Mucuna in Experiment 1. However, cooking, and soak and cook methods of detoxification slightly improved the nutritive value of Mucuna at 100 and 200gkg-1, respectively. Thus indicating partial or incomplete detoxification of the seeds. Further detoxification studies to ascertain the best processing method for improved feeding value of the seed is therefore needed. Increasing the cooking time and cooking in alkaline or acid solution may be helpful in the regard.